Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
bằng 128 vì 9 + 9 + 9 + 18 + 7 + 5 + 2 + 48 + 21= ( 9 + 21) + ( 48 + 2) + ( 9 + 9 ) + 18 + 7 + 5
= 30 + 50 + 18 + 18 + 7 + 5
= 80 + ( 18x 2) +( 7 + 5 )
= 80 + 36 + 12
= 80 + 48
= 128
`1)1/2:2/3 .... 2/3 : 1/2`
`=>1/2xx3/2 .... 2/3xx2`
`=>3/4 .... 4/3`
Vì `3/4 < 1` và `4/3>1`
`=>3/4<4/3`
__
`4/7:2/5 ... 4/7 : 3/5`
`=>4/7xx5/2....4/7xx5/3`
`=>20/14...20/21`
`=>10/7...20/21`
Vì `10/7>1` và `20/21<1`
`=>10/7>20/21`
__
`4/15:4/7....2/5xx10/3`
`=>4/15xx7/4...20/15`
`=>7/15...20/15`
Vì `7<20` nên `7/15<20/15`
__
`5/6...15/18-11/18`
`=>5/6...4/18`
Ta có : MSC : `18`
`5/6 = 15/18`
Vì `15>4` nên `5/6 > 4/18`
a. \(\left(2-\frac{2}{17}\right)\times\frac{51}{64}\)
\(=\frac{22}{17}\times\frac{51}{64}\)
\(=\frac{22\times51}{17\times64}=\frac{1122}{1088}=\frac{561}{544}\)
b. \(\left(\frac{2}{5}+\frac{5}{7}\right)\times\frac{5}{13}\)
\(=\frac{39}{35}\times\frac{5}{13}\)
\(=\frac{3}{7}\)
c. \(\frac{13}{18}\div\left(\frac{7}{12}-\frac{4}{9}\right)\)
\(=\frac{13}{18}\div\frac{28}{27}\)
\(=\frac{13}{18}\times\frac{27}{28}=\frac{39}{56}\)
#z
\(\left(2-\frac{2}{17}\right)\times\frac{51}{64}\)
\(=\frac{32}{17}\times\frac{51}{64}\)
\(=\frac{1632}{1088}=\frac{3}{2}\)
\(\left(\frac{2}{5}+\frac{5}{7}\right)\times\frac{5}{13}\)
\(=\left(\frac{14}{35}+\frac{25}{35}\right)\times\frac{5}{13}\)
\(=\frac{39}{35}\times\frac{5}{13}\)
\(=\frac{195}{455}=\frac{3}{7}\)
\(\frac{13}{18}:\left(\frac{7}{12}-\frac{4}{9}\right)\)
\(=\frac{13}{18}:\left(\frac{63}{108}-\frac{48}{108}\right)\)
\(=\frac{13}{18}:\frac{5}{36}\)
\(=\frac{13}{18}\times\frac{36}{5}\)
\(=\frac{468}{90}=\frac{26}{5}\)
a,17/23 + (1 - 17/23)
= 17/23 + 6/23
= 23/23 = 1
b,17/12 + 9/7 - (2/7 + 5 /12)
= (17/12 - 5/12) + (9/7 + 2/7)
= 1+1 = 2
c, 7/13 - ( 4/7 -6/13 )
= 7/13 - 4/7+ 6/13
= (7/13 + 6/13) -4/7
= 13/13 -4/7
= 1 -4/7 = 3/7
hok tốt✍️ ✍️
a) 17/23+(1-17/23)
=17/23+1-17/23
=1
b)17/12+9/7-(2/7+5/12)
=17/12+9/7-2/7-5/12
=1+1
=2
c)
7/13-(4/7-6/13)
=7/13-4/7+6/13
=1-4/7
=3/7
a) 17/23 + (1 - 17/23)
= 17/23 + 1 - 17/23
= (17/23 - 17/23) + 1
= 0 + 1 = 1
b) 17/12 + 9/7 - (2/7 + 5/12)
= 17/12 + 9/7 - 2/7 - 5/12
= (17/12 - 5/12) + (9/7 - 2/7)
= 1 + 1 = 2
c) 7/13 - (4/7 - 6/13)
= 7/13 - 4/7 + 6/13
= (6/13 + 6/12) - 4/7
= 1 - 4/7 = 3/7
d) 7/18 + 3/16 + 11/18 + 13/16
= (7/18 + 11/18) + (3/16 + 13/16)
= 1 + 1 = 1
d) sửa 7/18 + 3/16 + 11/18 + 13/16
= (7/18 + 11/18) + (3/16 + 13/16)
= 1 + 1
= 2
Lay (59/18 + 46/9) + (75/14 + 15/7) + (5/2 + 47/18)
De et a
11/18 nha
=\(\dfrac{7}{18}+\dfrac{2\times2}{9\times2}\)
=\(\dfrac{7}{18}+\dfrac{4}{18}\)
=\(\dfrac{11}{18}\)